2020
DOI: 10.3390/vaccines8040724
|View full text |Cite
|
Sign up to set email alerts
|

The Immunogenic and Immunoprotective Activities of Recombinant Chimeric T. gondii Proteins Containing AMA1 Antigen Fragments

Abstract: Toxoplasmosis, one of the most common parasitoses worldwide, is potentially dangerous for individuals with a weakened immune system, but specific immunoprophylaxis intended for humans is still lacking. Thus, efforts have been made to create an efficient universal vaccine for both animals and humans to overcome the shortcomings of currently used treatment methods and protect all hosts against toxoplasmosis. The current work represents a relatively new approach to vaccine development based on recombinant chimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…AMA1, only expressed in the Toxoplasma-tachyzoite stage, has an immunogenicity and high pathogenicity compared to other AMAs [23]. Three tetravalent chimeric proteins containing different portions of the parasite's AMA1 antigen-AMA1 domain I -SAG2-GRA1-ROP1 L (A N SGR), AMA1 domains II , III-SAG2-GRA1-ROP1 L (A C SGR) and AMA1 full protein -SAG2-GRA1-ROP1 L (A F SGR)-were evaluated for their immunogenic and immunoprotective potentialities [132]. All evaluated proteins were immunogenic and triggered specific humoral and cellular immune responses in vaccinated mice.…”
Section: Apical Membrane Antigens (Amas)mentioning
confidence: 99%
See 1 more Smart Citation
“…AMA1, only expressed in the Toxoplasma-tachyzoite stage, has an immunogenicity and high pathogenicity compared to other AMAs [23]. Three tetravalent chimeric proteins containing different portions of the parasite's AMA1 antigen-AMA1 domain I -SAG2-GRA1-ROP1 L (A N SGR), AMA1 domains II , III-SAG2-GRA1-ROP1 L (A C SGR) and AMA1 full protein -SAG2-GRA1-ROP1 L (A F SGR)-were evaluated for their immunogenic and immunoprotective potentialities [132]. All evaluated proteins were immunogenic and triggered specific humoral and cellular immune responses in vaccinated mice.…”
Section: Apical Membrane Antigens (Amas)mentioning
confidence: 99%
“…However, the intensity of the produced immune protection depended on the fragment of the AMA1 antigen incorporated into the chimeric antigen's structure. It has been identified that full length AMA1 can trigger further potent immunity in mice, resulting in significantly increased survival and partial protection against Toxoplasma cyst formation [132]. Furthermore, the full-length AMA1 and two different fragments (AMA1N and AMA1C) have been tested for the detection of IgG and IgM anti-Toxoplasma antibodies in human and mouse immune sera in ELISA assays [133].…”
Section: Apical Membrane Antigens (Amas)mentioning
confidence: 99%
“…Synthetic B and T cell epitopes of GRA2 can partially protect immunized mice against an ME49 challenge infection [ 62 ]. Chimeric protein vaccine comprising fragments of AMA1 fused to SAG1, GRA2, and ROP1 were assessed, with all of the generated chimeric vaccines conferring decent levels of humoral and cellular immune responses [ 63 ]. Similarly, protein vaccines based on B and Th cell epitopes of T. gondii aspartic protease 3 promoted the production of Th1 cytokines and prolonged survival for as long as 18 days after a challenge infection with the virulent RH strain [ 64 ].…”
Section: Vaccine Platforms Against T Gondiimentioning
confidence: 99%